2004
DOI: 10.2472/jsms.53.1109
|View full text |Cite
|
Sign up to set email alerts
|

Microcracking and Compressive Strength Degradation of Carbon Fiber/Polyimide Resin Composites by Thermal Cycling

Abstract: The objective of this study was to investigate the effect of thermal cycles, encountered by an Super Sonic Transport (SST) in service, on the cumulative frequency of microcracks and the degradation of compressive strength in carbon fiber/polyimide resin composite materials.One thermal cycle was designated as a sequence from room temperature finally back to RT. Transverse microcracks initiated on the sectional free edge surface of the laminates were observed and counted by using an optical microscope. Approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Carbon Fiber Reinforced Plastic (CFRP), which has a high level of specific stiffness and strength, is focused on as a structural material for reusable launch vehicles, which will be used under water and in thermal cycling environments. Therefore, the effects of water absorption [1][2][3][4][5][6][7] and thermal cycling [8][9][10] on the mechanical properties of CFRP have been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon Fiber Reinforced Plastic (CFRP), which has a high level of specific stiffness and strength, is focused on as a structural material for reusable launch vehicles, which will be used under water and in thermal cycling environments. Therefore, the effects of water absorption [1][2][3][4][5][6][7] and thermal cycling [8][9][10] on the mechanical properties of CFRP have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The flexural property and Mode I interlaminar fracture toughness of CFRP after water absorption and freezing decreased with an increase in immersion time. Katoh et al [8] reported on the compressive strength of CFRP during thermal cycling, which decreased with an increase in the number of cycles because of the initiation of cracks in CFRP during thermal cycling. The mechanical properties of water absorbed CFRP during thermal cycling should be investigated in respect of its application as a structural material in reusable launch vehicles.…”
Section: Introductionmentioning
confidence: 99%